Clinical and Radiographic Outcomes of Supramalleolar Osteotomy for the Old Age Patients with Medial Compartment Ankle Osteoarthritis - Jung-Won Lim MD; Hong-Geun Jung MD PhD; Je-Min Im (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis Introduction/Purpose: Supramalleolar osteotomy (SMO) has recently been accepted as the major surgical option for treating painful asymmetric ankle arthritis. However, in many literatures, old age is regarded as relative contraindication for SMO. This study aimed to evaluate clinical and radiographic outcomes of medial compartment ankle osteoarthritis (OA) treated with SMO for the patients of relatively old age. Also, the study is aimed to compare the outcomes between old age group (≥ 65 years) and the group younger than 65 years. Methods: The study is based on consecutive 60 ankles of medial compartment ankle arthritis (60 patients) with moderate to severe medial ankle pain (at least 1-year follow-up). SMO and fibular valgization oblique osteotomy were performed. As for the functional evaluation, visual analogue scale (VAS) pain scores, American Orthopaedic Foot and Ankle Society (AOFAS) ankle- hindfoot scores and ankle range of motion (ROM) were evaluated. On radiographs, tibial anterior surface angles (TAS), tibial lateral surface angles (TLS), and talar tilt angles (TT) were measured and the severity of ankle OA was classified by the Takakura stage. To evaluate how the age affects the outcomes of SMO procedures, the subjects were classified as two groups (Group 1: ≥ 65 years, 14 ankles, Group 2: < 65 years, 46 ankles) and the comparison between the groups were made. Using second look arthroscopy, regeneration of articular cartilage was evaluated and compared between the groups. Results: The postoperative VAS pain score and ROM in group 1 were not inferior to those in group 2 (2.0 ± 2.0 vs 1.0 ± 1.4, p=0.949 / 50.7 ± 12.8 vs 52.0 ± 13.5, p=0.764). Also, the postoperative TLS angle and TT angle showed no significant difference between two groups. However, the postoperative AOFAS score was significantly higher in group 2 (79.0 ± 12.6 vs 88.0 ± 9.4, p< 0.05). In terms of delayed union, there was no significant difference between two groups (3/14, 21.4% vs 9/46, 19.6%, p=0.818). As to complication rate, there was also no significant difference between two groups (1/14, 7.1% vs 6/46, 13.0%, p=0.899). There were no significant difference according to articular cartilage regeneration after SMO between two groups. Conclusion: SMO for the relatively older patients with painful medial compartment ankle OA achieved favorable clinical and radiological outcomes. In terms of osteotomy site union and complications, older age group (≥ 65 years) showed the results not inferior to those of younger age group ( < 65 years). Even in the older age group, SMO could be one of the surgical options for the medial ankle OA.